PSXIII-14 Use of enzyme technology to improve nutritive value of corn modified distillers grains. (7th December 2018) - Paulus Compart, D; Anele, U; Engel, C
Abstract: In vitro and in situ techniques were used in the present study to evaluate the potential of enzymes to improve dry matter digestibility (DMD) of corn modified distillers grains (MDG) in feedlot diets. Eight exogenous enzymes (alpha-amylase, cellulase, mannanase, protease, xylanase, Aspergillus niger extract, Aspergillus oryzae extract, and a combination of A. oryzae and A. niger extract) were evaluated in the present study at 5 levels of inclusion (2, 4, 6, 8 and 10 g/hd/d) using the in vitro batch culture technique. In vitro dry matter digestibility (IVDMD) was measured at 6, 12 and 24 h of incubation using rumen fluid from 3 cannulated beef steers fed a high concentrate diet. It was hypothesized that inclusion of enzymes would improve digestibility of a MDG based feedlot diet. There was no interaction (P>0.05) between enzyme treatment and level of inclusion for IVDMD. Additionally, inclusion level had no effect (P=0.916) on IVDMD. Dry matter digestibility was highest (P=0.036) for the protease treatment which resulted in an increase of 9.3% IVDMD compared with the control (no enzyme). Based on the in vitro batch culture results, cellulase, protease and Aspergillus oryzae extract (increased IVDMD of 7.7, 9.3 and 6.0% respectively compared to control) were selected for further evaluation using the in situ technique. For the in situ study, these 3 enzymes were compared with a control treatment (no enzyme) and incubated for 6, 12 and 24 h in the rumen of 3 cannulated steers. Compared with the control, all the enzyme treatments had higher (Pin vitro batch culture result, protease inclusion resulted in an increase of 9.9% ruminal DMD (versus 9.3% for IVDMD). Overall, these two techniques were utilized to identify an exogenous enzyme (protease) that can potentially increase dry matter and fiber digestibility of MDG in feedlot cattle. Key Words: